As You Like It - Shakespeare, William; Edited By Gill, Roma (New York Oxford University Press, 2009)
As You Like It is a popular text for study by secondary students the world over. This edition includes illustrations, preliminary notes, reading lists (including websites) and classroom notes.
Include Illustrations